The Locator Framework for Detecting Movement Indoors - Kevin Curran (Universitas Ahmad Dahlan, 2018)
There are many advantages to being able to track in real-time the movement of things or humans. This is especially important in tracking goods in the supply chain, in security and also in health and safety. The Global Positioning Satellite (GPS) system works well in outdoor environments but it cannot track items indoors. There is also the problem of power hungry sensor chips inherent in some GPS trackers. Mobile Cellular triangulation also works well for many outdoor solutions but problems with cost, accuracy and reliability make it difficult to deploy for indoor tracking scenarions. The levels of accuracy can vary by up to 50 meters which hinder its ability for adoption in many use case scenarios. There are also problems with poor cellular coverage in rural areas. Solutions built on WiFi–the IEEE 802.11 standard overcome many of these issues. WiFi location tracking works via sampling of the received signal strength (RSS) which along with triangulation and prior mapping allows systems to locate items or humans with fine-granularity. This WiFi fingerprinting is a viable cost-effective approach to determining movement within indoor enviroments. This paper presents an overview of popular techniques and off-the-shelf solutions which can be used to determine movement of people and objects indoors. We outline the Locator frameworks which is built on both active and passive indoor localisation techniques for tracking movement within indoor environments.